Upaya Pencegahan Penyakit Hipertensi melalui Pemeriksaan Tekanan Darah dan Pendidikan Kesehatan Pencegahan Hipertensi di Desa Curah Cottok, Situbondo - Made Indra Ayu Astarini; Ira Ayu Maryuti; Kristina Pae (LPMP Imperium, 2023)
This community service activity aims to increase the knowledge of the elderly regarding the prevention of hypertension, which often occurs in the elderly because, in the elderly, there is a decrease in the elasticity of blood vessels, so they are at high risk of experiencing hypertension. Hypertension can have an impact on the quality of life of the elderly. Prolonged hypertension will cause heart pumping disorders, kidney disease, and neurological diseases. The method used in this activity is in the form of lectures giving health education about hypertension prevention and health checks in measuring blood pressure as early detection of hypertension in the elderly. Participants were given health education utilizing lectures and media like leaflets and posters. Participants are allowed to ask questions if something needs to be understood. Participants in the activity were the elderly and pre-elderly (≥55 years) in Curah Cottok, Situbondo.